Biological and Community Health Determinants of Childhood Anemia: A Cross-Sectional Study in Primary Schools in Mosul, Iraq - Dawood, Yousif Qasim (Indonesian Journal on Health Science and Medicine, 2025)
Childhood anemia is a major global health issue, impairing growth, cognitive development, and immune function. Its prevalence is particularly concerning in post-conflict regions where healthcare infrastructure, nutrition, and sanitation are compromised. In Mosul, Iraq, years of conflict and displacement have heightened children’s vulnerability to nutritional deficiencies and infections, yet localized epidemiological data remain scarce. Limited evidence exists on the combined biological and community health determinants of anemia in Iraqi primary school children, restricting effective intervention planning. This study aimed to determine the prevalence of anemia among school-aged children in Mosul and identify its key biological and socio-environmental determinants. Results: A cross-sectional study of 850 children aged 6–12 years revealed an overall anemia prevalence of 42.5%, with mild anemia as the most common form (65.1%). Logistic regression analysis identified low maternal education (OR = 2.34, p < 0.001), low household income (OR = 2.16, p < 0.001), infrequent red meat intake (<2 times/week, OR = 2.80, p < 0.001), stunting (OR = 3.50, p < 0.001), and a history of parasitic infection (OR = 2.10, p = 0.003) as significant predictors. This is among the first large-scale studies in Mosul to integrate both biological and community-level determinants of anemia, reflecting the multifactorial nature of the condition in post-conflict settings. The findings underscore the urgent need for multisectoral interventions, including nutritional supplementation, deworming, health education, and sanitation improvements, to combat childhood anemia and improve long-term child health outcomes in Mosul. Highlights: Childhood anemia prevalence in Mosul primary schools was 42.5%, classifying it as a severe public health problem. Key determinants included low maternal education, low household income, infrequent red meat consumption, stunting, and parasitic infections. Findings highlight the urgent need for multisectoral interventions combining nutrition, deworming, education, and sanitation improvements.